An Analysis of al-Bay’ Bithaman Ajil Contract in Islamic Financing Products: A Case Study in Brunei - MUWAZIR, MOHD RIZAL; HASSAN, HAJAH SABARIAH HAJI; HADI, NORADILAH ABDUL; SRI WIDYASTUTI; SAID, MOHAMMAD (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to analyse factors influencing the application of the al-bay’ bithaman ajil (BBA) contract which is still dominating financing instruments in Islamic financial institution in Brunei Darussalam (Brunei). This study employs case study research design which entirely concentrates on qualitative analysis from interview technique as a primary data collection method. There were 10 respondents selected in this study working in Tabung Amanah Islam Brunei (TAIB). The results suggest that respondents were very optimistic and hold positive ideas towards the implementation of other forms of Shariah contracts in Islamic financial products, which have now been introduced in other countries. The article provides valuable contribution to the development of Islamic finance in Brunei. Following the controversy surrounding the use of BBA contract in other countries, the result of this study will offer Islamic financial institutions and regulators in Brunei positive development in the effort to diversify Islamic financing products and services which are universally accepted according to current demands.